Radial and Angular Resolved Langmuir Probe Diagnosis of a Pulsed Vacuum Arc Plasma - 陈磊 马明旺 黎明 金大志 谈效华 戴晶怡 杨林 胡思得 (Plasma science & technology, 2011)
Vacuum arc ion sources are known for delivering high currents of ion beams in many technological applications. There is a great need in the present ion accelerator injection research for a titanium vacuum arc source to produce high-ionized plasma, in which its parameter is extremely important to match the extractors geometry and the extraction voltage. In this paper, the radial and angular distributions of the titanium cathodic vacuum arc plasma parameters are measured by a cylindrical Langmuir probe and analyzed by the Druyvesteyn method from the I-V curves. The electron density ne is about 10^（17）m^（-3） and the effective electron temperature Tefr is in the range of 6.12-11.11 eV in the free expansion cup before the ion extraction. The measured distribution of ne over the expansion cross-section is non-uniform and axially unsymmetrical with its form similar to the Gaussian distribution, and most of the plasma is concentrated into an area whose radius is smaller than 5 mm. Teff has a nearly uniform distribution over the expansion cross-section during the discharge. The results of the plasma parameters＇ non-uniformity encourage the researchers to make some optimization designs to improve the parameter distributions, and then to facilitate ion extraction.